The Influence of Perceived Environmental Impacts of Tourism on the Perceived Importance of Sustainable Tourism - Nejati, Mehran; Mohamed, Badaruddin; Shida Irwana, Omar (2015)
Efforts for investigating perception towards tourism and its perceived negative impacts have mainly been conducted from the perspective of locals, often ignoring the perception of tourists on the negative environmental outcomes associated with tourism and its link with the perceived importance of sustainable tourism from the eyes of tourists. This study investigated the perception of tourists of the potential impacts of tourism on the natural environment. Additionally, it examined the influence of perceived environmental impacts of tourism on the perceived importance of sustainable tourism. The study model was analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) based on data collected from 469 tourists visiting two attractive islands in Malaysia, namely Perhentian Island and Redang Island. Findings of this research revealed that perceived impacts of tourism on vegetation, water quality and wildlife had significant influence on the tourists’ perceived importance of sustainable tourism, while the environmental impacts of tourism on soil, sand and rock, air quality and landscape did not have any significant influence on the perceived importance of sustainable tourism. Sustainable tourism in this study was limited to environmentally sustainable tourism. Study implications are discussed.